2007
DOI: 10.1097/ta.0b013e318033a790
|View full text |Cite
|
Sign up to set email alerts
|

A Ten-Year Retrospective Review: Does Pyloric Exclusion Improve Clinical Outcome After Penetrating Duodenal and Combined Pancreaticoduodenal Injuries?

Abstract: In our study population, the performance of pyloric exclusion for penetrating advanced duodenal injury and combined pancreatic and duodenal injuries did not improve clinical outcome. The trend toward a greater overall complication rate, pancreatic fistula rate, and increased length of hospital stay in the pyloric exclusion group suggests that simple repair without pyloric exclusion is both adequate and safe for most penetrating duodenal injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
1
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 20 publications
2
71
1
8
Order By: Relevance
“…The authors concluded that simple repair without pyloric exclusion was both adequate and safe for most penetrating duodenal injuries. 7 Their report presented significant study limitations, as recognized by the authors. It was retrospective and the patients were not randomized, thus suggesting that pyloric exclusion could have been applied to higher-risk patients.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The authors concluded that simple repair without pyloric exclusion was both adequate and safe for most penetrating duodenal injuries. 7 Their report presented significant study limitations, as recognized by the authors. It was retrospective and the patients were not randomized, thus suggesting that pyloric exclusion could have been applied to higher-risk patients.…”
Section: Discussionmentioning
confidence: 89%
“…The overall mortality rate for duodenal injuries remains between 5.3% and 30%, but injuries to the duodenum itself are responsible for a mortality rate of about 10%. 1,2,4 A recent study by Seamon et al 7 examined patients with penetrating duodenal injuries of grade ≥ II and pancreaticoduodenal injuries, excluding patients who died within 48 hours due to massive associated injuries. Fifteen out of their 29 patients were treated without pyloric exclusion and 14 with exclusion, and the groups were similar with regard to sex, age, mechanism, hemodynamic stability, injury grade (a trend toward greater injury severity was noted in the pyloric exclusion group), ISS, associated abdominal injuries and mortality rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Degiannis et al 26 , em estudo em que indicaram a exclusão pilórica, concluíram que este procedimento deve ser indicado em lesões Grau III causadas por FPAF. Já Seamon et al 27 compararam retrospectivamente em pacientes com trauma penetrante de duodeno Grau > II ou lesões duodenopancreáticas, o reparo primário associado ou não à exclusão pilórica, e observaram uma maior incidência de complicações em pacientes tratados com exclusão pilórica, desaconselhando o uso deste procedimento. Atualmente existem na literatura controvérsias sobre o uso de exclusão pilórica, e estudos prospectivos se fazem necessários para dirimir estas dúvidas.…”
Section: Mecanismo De Traumaunclassified